The Parameters of the Working Organ of the Furrow Opener Were Determined Based on the Application in the Combined Machine - Amanullayevich, Abdirakhmanov Ravshanbek; ugli, Abdumannopov Abdullo Makhamadsoli (American Journal of Biodiversity, 2025)
In the field of agricultural mechanization, the level of use of combined machines capable of performing several technological processes in one run is increasing every day. In this article, the parameters of the working part of the furrow cutter used in the combined machine, which can be used in the inter-row spaces of orchards, are theoretically studied.